Javanese House Interior Study: A Philosophical and Cosmological Extraction of Java’s Heritage, as Design Principles Application in Local Content Context - Fajarwati, Ade Ariyani Sari (Humaniora, 2017)
Omah has interior arrangement system and regulation according to the life of Javanese people hereditarily. In its process of building and interior arranging, Javanese people hold on to the philosophical and cosmological concept, which was illogic for modern design study to be applied in the aesthetic study. This study aimed to examine the extent of the correlation between consideration of philosophical and cosmological Java community with modern design principles in making Omah. It was through observation on concept application to the realization in Omah form and also through literature analysis of both these principles. This research used the qualitative method in the form of observation and literature study. This research would observe and analyze the relationship between philosophical and cosmological extraction of Javanese interior with design principle through the study from another journal. It finds that a design that facilitates activities and way of life of Javanese people applies design principles and a modern study that becomes visual beauty guidance.